2021
DOI: 10.1039/d1fo01966j
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and lipid lowering effects of theaflavins in high-fat diet-induced obese mice

Abstract: Theaflavins (TFs) are the characteristic components of black tea and have been widely acquainted for their health benefits. The current study aimed to investigate the effects and mechanism of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…SIRT6 is an NAD + -dependent deacetylase regulating hepatic glucose and lipid metabolism [ 24 ]. Cai et al reported that theaflavins decreased the expression of SIRT6 to reduce lipid accumulation [ 49 ]. Khan et al confirmed that SIRTP6 regulates fatty acid transport by inhibiting PPARγ [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 is an NAD + -dependent deacetylase regulating hepatic glucose and lipid metabolism [ 24 ]. Cai et al reported that theaflavins decreased the expression of SIRT6 to reduce lipid accumulation [ 49 ]. Khan et al confirmed that SIRTP6 regulates fatty acid transport by inhibiting PPARγ [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a recent time, the effect of TFs extracted and purified from black tea was studied in high-fat diet–induced obese mice, and the results demonstrated that gavage administration of TFs might exert antihyperglycemic and lipid-lowering effects by inhibiting the synthesis and accumulation of lipids in the liver with activation of related pathways. Compared to other monomers of theaflavins, TF3 was proved to be the best choice ( Cai et al, 2021 ). Our previous research in vitro also reported that TF3 is the best one among the theaflavin constituents in alleviating hepatocyte lipid deposition through activating an AMPK signaling pathway by inhibiting plasma kallikrein ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A TF mixture (25 mg/kg/day) improved impaired glucose tolerance and significantly lower blood glucose levels in prediabetic SDT rats, and increased insulin expression via the inhibition of gastric inhibitory polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) degradation [ 52 ]. Treatment with TFs reduced blood glucose levels and improved insulin resistance in mice, significantly reduced serum total cholesterol (TC), total cholesterol (TG), and low-density lipoprotein (LDL) levels, and inhibited alanine amino transferase (ALT), aspartate amino transferase (AST) activity [ 51 ]. The expression levels of sterol regulatory element-binding transcription factor 1 (SREBP-1), fatty acid synthase (FASN), which increases the expression of sirtuin 6 (SIRT6), were increased [ 51 ] High-fat diets and streptozotocin-induced diabetic rats were treated with different doses of TFs (25, 50, and 100 mg/kg b.wt/day) for 30 days, which resulted in glycated hemoglobin, hemoglobin, and glycoproteins (hexose, hexosamine, polystyrene and sialic acid), TCA cycle enzymes (isocitrate dehydrogenase, a-ketoglutarate dehydrogenase, succinate dehydrogenase and malate dehydrogenase) returned to near-normal levels, and the decreased homeostatic model assessment of insulin resistance (HOMA-IR) index in a dose-dependent manner [ 53 ].…”
Section: Metabolic Syndrome and Theaflavinsmentioning
confidence: 99%